REVIVING FRENCH ARPITAN: RECOMMENDATIONS TO REVITALIZATION EFFORTS - TAN, Youyansu (PEOPLE: International Journal of Social Sciences, 2020)
Arpitan, also known as Francoprovençal, is a severely endangered regional language with around 120,000-200,000 speakers, spoken at the crossroads of France, Italy, and Switzerland. This paper is a review of the literature on the current linguistic situation of Arpitan. It first presents an overview of current Arpitan revitalization efforts, along with potential impediments and favorable conditions of revitalization. At last, it proposes consultative advice on where to direct Arpitan revitalization efforts and how. Previous literature on Arpitan focuses mainly on the vitality of the language and its usage; however, there is an insufficient analysis on behalf of revitalization efforts. Thus, this paper, written from an outsider’s perspective, aims to bridge the gap between linguistic knowledge and practical advice on revitalization. This review could be potentially useful as a reference for Arpitan activists in France as they plan revitalization projects. It is hoped that the paper would update the linguistic community on the status of Arpitan and inform Arpitan revitalization activists from a third-party point of view.